Effect of Using Dialogue Technique in Teaching Speaking at Eighth Grade of MTs N 7 Pasaman Barat - Desantri, Sovia; Dewi, Merry Prima; Syahrul, Syahrul; Eliza, Eliza (ARZUSIN, 2023)
The purpose of this research was to determine the effect of using dialogue technique in teaching speaking. The researcher has done at MTsN 7 Pasaman Barat. This research was carried out because the students had some problems in speaking English. It was caused by several factors there were the students had difficulties to say something or express their idea. Then, the students had limited vocabulary, so the students did not speak English well. Besides that the students lack of confidence in speaking and have low pronunciation ability. In addition the teacher used monotonous ways in students speaking practice. In this research a quasi-experimental design was used by the researcher. The researcher used pre-test and post-test to experimental class and control class. The population of this research was the eighth grade students of MTsN 7 Pasaman Barat. The sample was 8B as experimental class taught by using dialogue technique and 8A as control class and taught without using dialogue technique. To determine the sample, the experimental and control class, the researcher utilized SPSS 20 to examine the data and check for normality and homogeneity. The researcher utilized the t-test formula to test the hypothesis and consulted the results in a t-table with level of significance of 0.05. From the calculation of the research the pre-test and post-test score in experiment class, it was found that there was a significant effect of using dialogue technique in teaching speaking. It was proven by the value t-calculated of experimental class in pre-test and post-test was higher than t-table (6.042 > 2.021). Then there was a significant difference between students who were taught using dialogue technique and those who were taught without them. The value of t-calculated in post-test from the experimental and control classes was greater than t-table (5.883 > 2.021). The last hypothesis was that teaching with dialogue technique was higher than teaching without dialogue technique in terms of improving students speaking skill. In the post-test, the mean score of the experimental class was greater than the control class (14.174 > 0.174).